Case Report: Azathioprine: An Old and Wronged Immunosuppressant - Chocair, Pedro R.; Neves, Precil Diego Miranda de Menezes; Mohrbacher, Sara; Neto, Maurilio Pacheco; Sato, Victor A. H.; Oliveira, Érico S.; Barbosa, Leonardo V.; Bales, Alessandra M.; Silva, Fagner Pereira da; Cuvello-Neto, Américo L.; Duley, John A. (Frontiers in Immunology, 2022)
Introduction: Mycophenolate rapidly substituted azathioprine (AZA) in transplant immunosuppression regimens since the 1990s, when early clinical trials indicated better outcomes, although opposite results were also observed. However, none of these trials used the well-established optimization methods for AZA dosing, namely, thiopurine methyltransferase pharmacogenetics combined with monitoring of the thiopurine metabolites 6-thioguanine nucleotides (6-TGN) and 6-methylmercaptopurine (6-MMP). Resistance to optimize AZA therapy remains today in transplant therapy, despite the fact that thiopurine metabolite testing is being used by other medical disciplines with evident improvement in clinical results. In a previous analysis, we found that active 6-TGN metabolites were not detectable in about 30% of kidney transplant patients under continuous use of apparently adequate azathioprine dosage, which demonstrates the need to monitor these metabolites for therapeutic optimization. Two of four case studies presented here exemplifies this fact. On the other hand, some patients have toxic 6-TGN levels with a theoretically appropriate dose, as seen in the other two case studies in this presentation, constituting one more important reason to monitor the AZA dose administered by its metabolites. This analysis is not intended to prove the superiority of one immunosuppressant over another, but to draw attention to a fact: there are thousands of patients around the world receiving an inadequate dose of azathioprine and, therefore, with inappropriate immunosuppression. This report is also intended to draw attention, to clinicians using thiopurines, that allopurinol co-therapy with AZA is a useful therapeutic pathway for those patients who do not adequately form active thioguanine metabolites.